Alkali-treatment of Lupine peels for valorizing adsorption of organic cationic pollutants from wastewater: Kinetics, isotherm, thermodynamic, regeneration, and mechanism - Nour W. Sabry; Ibrahim Naeem; Seed A. Hassanien; Osama Abuzalat; Ahmad Baraka (Next Materials)
Vegetable and fruit peels are gaining attention as economical and effective adsorbents for organic pollutants. This study highlights the potential of alkaline-treated Yellow Lupine Peels Powder (T-YLPP) as a biomaterial for removing cationic methylene blue (MB) from wastewater through adsorption. Characterization of untreated (YLPP) and NaOH-treated (T-YLPP) samples using FTIR, BET, SEM/EDX, and XPS revealed that alkaline treatment enhances functional group exposure, increases active sites, boosts surface area from 376.23 to 427.49 m²/g, and enlarges pore volume and size. Kinetic, isotherm, thermodynamic, and regeneration studies confirmed that MB adsorption by both samples is spontaneous, exothermic, and dominated by physical interactions, with pore diffusion controlling the process. The adsorption capacity of T-YLPP increased significantly from 3.99 mg/g (YLPP) to 46.51 mg/g. Effective regeneration was achieved through acid treatment combined with heating. The adsorption mechanism likely involves dipole-dipole interactions, hydrogen bonding, and cation exchange, making T-YLPP a promising candidate for wastewater treatment.